2022
DOI: 10.1136/jnis-2022-019662
|View full text |Cite
|
Sign up to set email alerts
|

Tenecteplase versus alteplase before mechanical thrombectomy: experience from a US healthcare system undergoing a system-wide transition of primary thrombolytic

Abstract: BackgroundTenecteplase (TNK) is a genetically modified variant of alteplase (TPA) and has been established as a non-inferior alternative to TPA in acute ischemic stroke (AIS). Whether TNK exerts distinct benefits in large vessel occlusion (LVO) AIS is still being investigated.ObjectiveTo describe our first-year experience after a healthcare system-wide transition from TPA to TNK as the primary thrombolytic.MethodsPatients with AIS who received intravenous thrombolytics between January 2020 and August 2022 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
13
2
Order By: Relevance
“…37 We observed no differential effect of tenecteplase versus alteplase on the incidence of ER across IVT-to-ER eval intervals in our analyses. This finding stands apart from some previous data that support that, while the ER rate quickly reaches about 20% with tenecteplase, even for short IVT-to-ER eval times, 18,21,27,37,39 it increases more slowly with alteplase. 28,39 While Figure 2 seems visually in favor of tenecteplase among patients with short IVT-to-ER eval times, the relevance of this trend is questionable given that nonlinear association was checked for in the continuous variable and that the interaction analysis was negative.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…37 We observed no differential effect of tenecteplase versus alteplase on the incidence of ER across IVT-to-ER eval intervals in our analyses. This finding stands apart from some previous data that support that, while the ER rate quickly reaches about 20% with tenecteplase, even for short IVT-to-ER eval times, 18,21,27,37,39 it increases more slowly with alteplase. 28,39 While Figure 2 seems visually in favor of tenecteplase among patients with short IVT-to-ER eval times, the relevance of this trend is questionable given that nonlinear association was checked for in the continuous variable and that the interaction analysis was negative.…”
Section: Discussioncontrasting
confidence: 99%
“…[19][20][21][22][23] Reduced process times have also been reported, owing to its simpler administration. [24][25][26] More recently, 2 nonrandomized studies reported higher ER rates with tenecteplase compared with alteplase, 27,28 while in the AcT trial (Alteplase Compared to Tenecteplase), both thrombolytics achieved similar ER rates. 29 Hence, there are conflicting data on whether tenecteplase actually yields higher ER rates than alteplase, and little data on potential differences in terms of ER predictors between the 2 agents.…”
mentioning
confidence: 99%
“…A retrospective study evaluated the system-wide impact in the USA of the transition from alteplase to TNK in patients with planned EVT. The study reported a significantly higher spontaneous recanalization rate in the TNK compared with the alteplase group (20 vs. 10%) [27].…”
Section: Current Evidence For Tenecteplase In Ischemic Strokementioning
confidence: 84%
“…Recently, tenecteplase, a newer thrombolytic agent that can be administered as a single bolus due to its longer half-life, has become more popular worldwide due to its ease of use. Past studies have suggested that tenecteplase may lead to a higher rate of LVR compared with alteplase 8 19. Thus, patients treated with tenecteplase may achieve LVR faster and/or more often than patients treated with alteplase, and future studies are needed to tailor the HALT score for predicting LVR in patients treated with tenecteplase.…”
Section: Discussionmentioning
confidence: 99%